2022
DOI: 10.3390/covid2040031
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Double-Blind, Placebo-Controlled Trial Evaluating Concentrated Phytochemical-Rich Nutritional Capsule in Addition to a Probiotic Capsule on Clinical Outcomes among Individuals with COVID-19—The UK Phyto-V Study

Abstract: Gut microflora dysbiosis affects the majority of individuals after COVID-19, contributing to both gastro-intestinal (GI) and non-GI symptoms. Natural phytochemicals have reported anti-viral properties and favourable effects on inflammatory and oxidative pathways, both important for tissue damage post-viral pneumonia. This study involved 147 participants with symptomatic COVID-19, randomised to receive a placebo (P) or a phytochemical-rich concentrated food capsule (PC) in addition to a pre/probiotic lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 137 publications
(240 reference statements)
0
8
0
Order By: Relevance
“…A small trial of sulodexide in individuals with endothelial dysfunction saw a reduction in symptom severity 169 . Pilot studies of probiotics indicated potential in alleviating gastrointestinal and non-gastrointestinal symptoms 170 , 171 . Two patients with long COVID experienced substantial alleviation of dysautonomia symptoms following stellate ganglion block 172 .…”
Section: Diagnostic Tools and Treatmentsmentioning
confidence: 99%
“…A small trial of sulodexide in individuals with endothelial dysfunction saw a reduction in symptom severity 169 . Pilot studies of probiotics indicated potential in alleviating gastrointestinal and non-gastrointestinal symptoms 170 , 171 . Two patients with long COVID experienced substantial alleviation of dysautonomia symptoms following stellate ganglion block 172 .…”
Section: Diagnostic Tools and Treatmentsmentioning
confidence: 99%
“…The results are promising and should prompt further longitudinal studies with more patients to investigate underlying pathomechanisms and changes in the microbiome of post-infectious fatigue patients. Especially in patients with Post-COVID19 conditions such studies will be helpful, as results of a recent study showed that the intervention with probiotics in combination with enzymes [ 55 ] or phyto preparations [ 56 ] was effective to reduce persistent symptoms and probiotic therapy during acute infection led to fewer symptoms compared to patients without such a treatment [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study gave probiotic capsules to people experiencing GI and non-GI symptoms of covid for an average of 108 days. It found that those given the probiotic (but not the control group) showed a significant improvement in cough, fatigue, and overall wellbeing, as well as in GI symptoms 10…”
Section: Can a Healthy Microbiome Reduce Covid Severity?mentioning
confidence: 99%